Competition adsorption of CO2/CH4 in shale: Implications for CO2 sequestration with enhanced gas recovery. (1st May 2023) - Liao, Qi; Zhou, Junping; Xian, Xuefu; Yang, Kang; Zhang, Chengpeng; Dong, Zhiqiang; Yin, Hong
Highlights: The competition adsorption behavior and adsorption models of CO2 /CH4 in shale were studied. The selectivity factor ( S C O 2 / C H 4 ) is generally greater than 1 in all the tested shale samples. S C O 2 / C H 4 generally decreased with the increase of pressure for most of the cases. S C O 2 / C H 4 first increased and then decreased with the increase of CO2 fraction in the gas mixture. The prediction accuracy of the adsorption model is in the order of IAST > E-L > LRC. Abstract: The competitive adsorption of CO2 /CH4 mixtures in shale is a prerequisite for optimizing the process of CO2 sequestration in shale with enhanced gas recovery (CO2 -ESGR). In this study, pure and binary adsorption of CH4 and CO2 in shale was measured at pressures up to 13 MPa and the temperature of 323.15 K using volumetric method. Pure and binary adsorption showed that CO2 is preferentially adsorbed in shale, and the adsorption amount of binary CO2 /CH4 increased with the increase of CO2 composition. The selectivity factor of CO2 over CH4 ( S C O 2 / C H 4 ) in all the tested samples is greater than 1 and closely related to the pressure and CO2 /CH4 concentration, as well as the CO2 phase state. S C O 2 / C H 4 generally decreased with the increase of pressure in the case of 50%CH4 + 50%CO2, while first decreased and then increased with the increase of pressure in the cases of 25%CH4 + 75%CO2 and 75%CH4 + 25%CO2 for most of the tested shale samples. The S C O 2 / C H 4 for most of tested shale samples in the case of 50%CH4 + 50%CO2 is the largest, and the S C O 2 / C H 4 in the case of 75%CH4 + 25%CO2 is greater than that in the case of 25%CH4 + 75%CO2, indicating that the S C O 2 / C H 4 initially increased then decreased with the increase of CO2 fraction. Thus, the CO2 is suggested to be injected when the reservoir pressure reduced to a certain level, and the injection pressure, rate and amount of CO2 should be optimized, to obtain an optimal S C O 2 / C H 4 to improve the efficiency of CO2 -ESGR and maximize the CO2 storage capacity. Furthermore, the binary CO2 and CH4 adsorption data were predicted using various models. The Ideal Adsorption Solution Theory (IAST) model fitted the experimental adsorption data the best, followed by the Extended Langmuir (E-L) and Loading Ratio Correlation (LRC). The results provide a firm basis for optimizing the CO2 injection strategies and estimating CO2 storage potential for CO2 -ESGR operation.